1999
DOI: 10.2307/3871041
|View full text |Cite
|
Sign up to set email alerts
|

The Phosphoenolpyruvate/Phosphate Translocator Is Required for Phenolic Metabolism, Palisade Cell Development, and Plastid-Dependent Nuclear Gene Expression

Abstract: The Arabidopsis chlorophyll a/b binding protein (CAB) gene underexpressed 1 (cue1) mutant underexpresses light-regulated nuclear genes encoding chloroplast-localized proteins. cue1 also exhibits mesophyll-specific chloroplast and cellular defects, resulting in reticulate leaves. Both the gene underexpression and the leaf cell morphology phenotypes are dependent on light intensity. In this study, we determine that CUE1 encodes the plastid inner envelope phosphoenolpyruvate/phosphate translocator (PPT) and defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
143
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(153 citation statements)
references
References 0 publications
10
143
0
Order By: Relevance
“…The transcriptional response of selected nuclear photosynthetic genes to variation in the excitation state of the two photosystems showed that the redox state of the plastoquinone pool controls the activity of the plastocyanin promoter (Pfannschmidt et al, 2001). The Arabidopsis ''chlorophyll a/b binding protein under-expression'' mutant cue1 offered additional evidence for the involvement of the redox state of the plastoquinone pool in the regulation of nuclear photosynthetic genes (Streatfield et al, 1999): lack of the CUE1-encoded phosphoenolpyruvate/phosphate translocator (PPT1) in the inner chloroplast envelope results in a reduced flux through the shikimate pathway and in a decrease in the plastoqinone pool, associated with an altered redox state of the thylakoids. The redox state of the stromal electron acceptors of PSI, in fact, seems to be crucial for the regulation of Lhcb genes (Pursiheimo et al, 2001).…”
Section: Redox Signallingmentioning
confidence: 99%
“…The transcriptional response of selected nuclear photosynthetic genes to variation in the excitation state of the two photosystems showed that the redox state of the plastoquinone pool controls the activity of the plastocyanin promoter (Pfannschmidt et al, 2001). The Arabidopsis ''chlorophyll a/b binding protein under-expression'' mutant cue1 offered additional evidence for the involvement of the redox state of the plastoquinone pool in the regulation of nuclear photosynthetic genes (Streatfield et al, 1999): lack of the CUE1-encoded phosphoenolpyruvate/phosphate translocator (PPT1) in the inner chloroplast envelope results in a reduced flux through the shikimate pathway and in a decrease in the plastoqinone pool, associated with an altered redox state of the thylakoids. The redox state of the stromal electron acceptors of PSI, in fact, seems to be crucial for the regulation of Lhcb genes (Pursiheimo et al, 2001).…”
Section: Redox Signallingmentioning
confidence: 99%
“…Overexpression of heterologous PPT2 or orthophosphate dikinase (PPDK) can partially complement the phenotype of ppt1. Thus, the cue1 mutant phenotype cannot simply be explained by a general restriction of the supply of plastids with PEP via the PPT (López-Juez 1998;Streatfield et al 1999;Voll et al 2003).In the present study, we characterized a T-DNA-tagged allele of the ppt1 mutant that was selected on the basis of its high chlorophyll fluorescence phenotype. We compared the photosynthetic behavior of different aged leaves of the ppt1 mutant at one developmental stage.…”
mentioning
confidence: 98%
“…The Arabidopsis ppt1 (or cue1) mutant is defective in AtPPT1 (at5g33320), which has been isolated in a screen for chlorophyll a/b binding protein (CAB) underexpressors (Li et al 1995; Knappe et al 2003). The affected gene in cue1 is a phosphoenolpyruvate (PEP)/phosphate translocator (PPT) of the plastid inner envelope membrane (Streatfield et al 1999). It appears that PEP is essential for plastid development and most nongreen plastids have been reported to be incapable of producing PEP from Calvin cycle intermediates (Flügge 1995; Voll et al 2002).…”
mentioning
confidence: 99%
See 2 more Smart Citations